Análise citoarquitetônica dos componentes do sistema de temporização circadiana do sagui (Calithrix jacchus), comparada com a inervação das suas principais aferências - Nascimento, Rayane Bartira Silva do (2011)
The suprachiasmatic nucleus (SCN) of the anterior hypothalamus, together with the intergeniculate leaflet (IGL) of the thalamus are considered the central components of the circadian timing system (CTS) of mammals. This system is responsible for the generation and regulation of circadian rhythms by establishing a temporal organization of physiological processes and behaviors. The neuronal specific nuclear protein (NeuN) has been widely used as a neuronal marker in several studies. Since glial fibrillary acidic protein (GFAP) is a component of intermediate filaments found in the cytoplasm of astrocytes and is commonly used as a specific marker for these cells. This study aims to identify, in the marmoset, the NeuN immunoreactive neurons and glial cells immunoreactive to GFAP, as well as map the major route of photic synchronization of the STC, retinohypothalamic tract (RHT), and identify the indirect pathway to the SCN and pregeniculate nucleus (PGN) - structure homologous to IGL rodents, using immunohistochemical and cytoarchitectonic techniques. Observed in SCN the presence of neurons immunoreactive to NeuN and terminals immunoreactive subunit b of cholera toxin (CTb), neuropeptide Y (NPY) and serotonin (5- HT). In the PGN noted the presence of the NeuN and NPY immunoreactive neurons and the immunoreactive terminals CTb and 5-HT. Astrocytes are present throughout the extent of the SCN and the PGN this New World primate